Expression of a fungal glucuronoyl esterase in Populus: Effects on wood properties and saccharification efficiency. (April 2015) - Latha Gandla, Madhavi; Derba-Maceluch, Marta; Liu, Xiaokun; Gerber, Lorenz; Master, Emma R.; Mellerowicz, Ewa J.; Jönsson, Leif J.
Graphical abstract: Glucuronoyl esterase Pc GCE from white-rot fungus Phanerochaete carnosa, an enzyme thought to hydrolyse the ester links between glucuronoyl substituents of xylan and alcohol groups in lignin, was overexpressed in hybrid aspen. The transgenic plants exhibited substantial increase in wood lignification. Enzymatic hydrolysis of cellulose in lignocellulose from the Pc GCE-overexpressing lines was expectedly reduced. However, the acidic pretreatment efficiently removed the inhibitory effects of lignin and the enzymatic hydrolysis following the acid pretreatment resulted in increased cellulose conversion by about 12% in the transgenic lines. This result indicates that intermolecular cross-linking targeted by Pc GCE inhibits enzymatic digestibility of lignocellulose. Highlights: A fungal glucuronoyl esterase was expressed heterologously in hybrid aspen. Transgenic lines compared to wild type exhibited higher contents of Klason lignin. Transgenic lines compared to wild type exhibited lower contents of 4- O -Me-GlcA, extractives, and cellulose. Transgenic lines compared to wild type exhibited reduced susceptibility to enzymatic hydrolysis without pretreatment. Transgenic lines compared to wild type exhibited higher glucan recovery in enzymatic hydrolysis after acid pretreatment. Abstract: The secondary walls of angiosperms contain large amounts of glucuronoxylan that is thought to be covalently linked to lignin via ester bonds between 4- O -methyl-α-d -glucuronic acid (4- O -Me-GlcA) moieties in glucuronoxylan and alcohol groups in lignin. This linkage is proposed to be hydrolysed by glucuronoyl esterases (GCEs) secreted by wood-degrading fungi. We report effects of overexpression of a GCE from the white-rot basidiomycete Phanerochaete carnosa, Pc GCE, in hybrid aspen ( Populus tremula L. x tremuloides Michx.) on the wood composition and the saccharification efficiency. The recombinant enzyme, which was targeted to the plant cell wall using the signal peptide from hybrid aspen cellulase Ptt Cel9B3, was constitutively expressed resulting in the appearance of GCE activity in protein extracts from developing wood. Diffuse reflectance FT-IR spectroscopy and pyrolysis–GC/MS analyses showed significant alternation in wood chemistry of transgenic plants including an increase in lignin content and S/G ratio, and a decrease in carbohydrate content. Sequential wood extractions confirmed a massive (+43%) increase of Klason lignin, which was accompanied by a ca. 5% decrease in cellulose, and ca . 20% decrease in wood extractives. Analysis of the monosaccharide composition using methanolysis showed a reduction of 4- O -Me-GlcA content without a change in Xyl contents in transgenic lines, suggesting that the covalent links between 4- O -Me-GlcA moieties and lignin protect these moieties from degradation. Enzymatic saccharification without pretreatment resulted in significant decreases of the yields of Gal, Glc, Xyl and Man in transgenic lines, consistent with their increased recalcitrance caused by the increased lignin content. In contrast, the enzymatic saccharification after acid pretreatment resulted in Glc yields similar to wild-type despite of their lower cellulose content. These data indicate that whereas Pc GCE expression in hybrid aspen increases lignin deposition, the inhibitory effects of lignin are efficiently removed during acid pretreatment, and the extent of wood cellulose conversion during hydrolysis after acid pretreatment is improved in the transgenic lines possible due to reduced cell wall cross-links between cell wall biopolymers by Pc GCE.